2020
DOI: 10.1167/iovs.61.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric, Hemodynamic, and Biomechanical Factors Influencing Blood Flow and Oxygen Concentration in the Human Lamina Cribrosa

Abstract: PURPOSE. We developed a combined biomechanical and hemodynamic model of the human eye to estimate blood flow and oxygen concentration within the lamina cribrosa (LC) and rank the factors that influence LC oxygen concentration. METHODS. We generated 5000 finite-element eye models with detailed microcapillary networks of the LC and computed the oxygen concentration of the lamina retinal ganglion cell axons. For each model, we varied the intraocular pressure (IOP) from 10 mm Hg to 55 mm Hg in 5-mm Hg increments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, significant negative associations were found for any given tissue, whether neural or connective (Figure 3). According to the biomechanical theory of glaucoma, 21 IOP-induced strain could potentially: (1) directly induce mechanical damage to the RGCs, 22 (2) disrupt the microcapillary blood flow at the LC, choroid and the retina [23][24][25] and (3) disrupt the axoplasmic flow. 26 Therefore, it would be plausible that eyes with structurally weaker ONHs (and thus higher strains) would be more susceptible to visual field loss.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significant negative associations were found for any given tissue, whether neural or connective (Figure 3). According to the biomechanical theory of glaucoma, 21 IOP-induced strain could potentially: (1) directly induce mechanical damage to the RGCs, 22 (2) disrupt the microcapillary blood flow at the LC, choroid and the retina [23][24][25] and (3) disrupt the axoplasmic flow. 26 Therefore, it would be plausible that eyes with structurally weaker ONHs (and thus higher strains) would be more susceptible to visual field loss.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 38 reported that the microvascular dropout in the parapapillary choroid has a strong relationship with initial PFS in POAG patients. Furthermore, Chuangsuwanich et al 39 investigated the link between the morphologic parameters and the hemodynamic changes of LC using finite-element analysis, and reported that the average oxygen concentration was lower in the central region than in the peripheral region of LC. In addition, when IOP was elevated, the oxygen concentration of LC declined and, notably, a greater cup depth and a weaker LC produced a lower oxygen concentration in LC.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, OCT, and its derivative elastography technique (optical coherence elastography [OCE]) [123,124], has superior spatial resolution, and in combination with biomechanical modeling, is a potent alternative for investigating ONH biomechanical properties in vivo [61 ▪▪ ,125 ▪ ,126]. Interestingly, OCT-driven morphologic reconstructions of the ONH can be used to generate patient-specific computer models to study ONH biomechanics [127] and hemodynamics [128], which may eventually be used as new tools for assessing progression of ONH pathological remodeling in glaucoma.…”
Section: The Role Of the Optic Nerve Head And Optic Nerve Sheath Biom...mentioning
confidence: 99%